PENGARUH PEMBERIAN KACANG PANJANG (Vigna unguiculata) TERHADAP KADAR GLUKOSA DARAH MENCIT (Mus musculus) YANG DIINDUKSI ALOKSAN (Effect of Long Bean (Vigna unguiculata) on Blood Glucose Level of Mice (Mus musculus) Induced by Alloxan) - Intan Fitri Aprila; M. Nur Salim; Razali Daud; T. Armansyah; Nuzul Asmilia; Faisal Jamin (Universitas Syiah Kuala, 2015)
The aim of this research was to find out the effect of long bean (Vigna unguiculata) on level of blood glucose on mice (Mus musculus) induced by alloxan. Twelve mice with the weigh of 25-40 grams and clinically healthy were used in this research. All mice were randomly divided into 4 treatment groups, 3 mice each. K0 was negative control group, only given aquadest. K1, K2, and K3 groups were induced by alloxan 0.5 ml. K1 group was positive control. K2 group was fed with 100 grams long bean mixed with 50 ml distilled water. K3 group was fed with 100 grams long bean mixed with 100 ml distilled water. Long bean was fed orally 0.5 ml every morning and evening for 7 consecutive days. On day eight the examination of blood glucose level was performed. The average level of blood glucose were K0 (142.00±23.39), K1 (167.00±10.54), K2 (122.67±12.50), dan K3 (154.67±16.26) mg/dL. In conclusion, the administration of long bean for seven consecutive days does not decrease blood glucose level on mice induced by alloxan.Key words: blood glucose, alloxan, long bean